Obtaining a filter irish lace marigold (Tagetes filifolia Lag.) sweetened with stevia leaves (Stevia rebaudiana Bertoni) - Millones, Carlos (2014)
The present investigation was conducted to determine the segment of the irish lace marigold and appropriate formulation of irish lace marigold and leaves of stevia in the development of a filter sweetened, for which plants were used irish lace marigold and leaves stevia, which were washed, disinfected, dried at 65 °C, ground, sieved and packed; later formulations were made with irish lace marigold and stevia leaves (90:10, 85:15, 80:20 and 75:25), using a gram per sample packed in sealable paper, the results of the color, infusion time and pH, also the organoleptic evaluations smell, taste, sweetness and overall appearance were processed using the SAS statistical package (Statistical Analysis System ) for Window V8. The results showed that using 80 to 85 % leaves + flowers irish lace marigold and 15 to 20% stevia leaf with a sweetened organoleptically suitable filter is obtained.